Komposisi Dan Kecernaan In Vitro Pakan Komplet Fermentasi Berbasis Pucuk Tebu Dan Gamal Pada Beberapa Lama Inkubasi - Susanti, Sri; Marhaeniyanto, Eko (Jurnal Ilmiah Fillia Cendekia, 2023)
Sugarcane shoots are potential animal feed but their nutritional value needs to be increased through a complete feed fermentation process. Research objectives to know the composition and digestibility value of fermented complete feed based on sugarcane shoots and plus Effective Microorganisms 4 (EM-4) as inoculants. The treatments consisted of four fermentation periods: 0 (F0), 7 (F7), 14 (F14) and 21 days (F21) with six repetitions, designed with Completely Randomized Design (CRD). Complete feed based on sugarcane shoots and gamal contains 12.42% crude protein (F0), higher than only sugarcane shoots (5.24%). Fermentation for 7 days produced complete feed with good texture and color, fresh sour and no mold was found. A decrease in chemical composition was found in complete feed with a fermentation time of 21 days although was not significants (P>0.05). Crude protein levels at F14 and F21 respectively 11.72% and 11.30% were lower than F0. From the in vitro test, the digestibility of dry matter (DDM) and organic matter (DOM) of fermented complete feed was higher than F0 (46.42± 5.34% and 40.97± 2.33%).The F14 treatment resulted in the highest in vitro DDM of 63.93±2.01% and the highest in vitro DOM of 55.85±1.40%, which then decreased in value in the F21. It be concluded that the fermentation time of 14 days (F14) produced complete fermented feed which was good organoleptically, crude protein content of 11.72%, and the best in vitro DDM and DOM.